2013
DOI: 10.1007/s00259-013-2482-z
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor PET/CT in neuroendocrine tumours: update on systematic review and meta-analysis

Abstract: SMSR PET has good diagnostic performance for evaluation of NET in the thorax and abdomen, better than SRS which has been the previous standard method. This meta-analysis gives further support for switching to SMSR PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(106 citation statements)
references
References 53 publications
1
101
0
4
Order By: Relevance
“…It may be argued that 68 Ga-based tracers such as 68 Ga-DOTATATE, 68 Ga-DOTATOC, or 68 Ga-DOTANOC would equally perform better than 111 In-DTPA-OC (30). Indeed, such comparative studies also found more foci identified with 68 Ga-based tracers than with SPECT (27,31,32).…”
Section: Discussionmentioning
confidence: 84%
“…It may be argued that 68 Ga-based tracers such as 68 Ga-DOTATATE, 68 Ga-DOTATOC, or 68 Ga-DOTANOC would equally perform better than 111 In-DTPA-OC (30). Indeed, such comparative studies also found more foci identified with 68 Ga-based tracers than with SPECT (27,31,32).…”
Section: Discussionmentioning
confidence: 84%
“…Somatostatin receptor PET/CT is increasingly used in patients with known or suspected neuroendocrine tumours demonstrating high diagnostic accuracy and is superior compared to 111 In-pentetreotide scintigraphy in this setting [6,7]. Recent articles in the literature assessed the diagnostic accuracy of somatostatin receptor PET/CT using different somatostatin analogues labelled with 68 Ga ( 68 Ga-DOTATATE, 68 Ga-DOTANOC and 68 Ga-DOTATOC) in patients with extraadrenal PGL [8][9][10][11][12][13][14][15][16][17], based on the increased expression of somatostatin receptors in PGL neoplastic cells [18].…”
mentioning
confidence: 99%
“…Somatostatin receptor PET/CT using somatostatin analogues labelled with gallium-68 is a valuable diagnostic tool for patients with neuroendocrine tumours (NETs) [21,22]. The experience with somatostatin receptor PET/CT in recurrent MTC is limited compared to FDG and F-DOPA [9].…”
Section: B)mentioning
confidence: 99%